A new AC OPF tool for sub‐transmission networks considering distribution switching actions and load‐transferring capability. (20th May 2019) - Tavakkoli, Mohammad Ali; Amjady, Nima
Abstract: In practical power systems, in order to study the results of optimal power flow (OPF) for a sub‐transmission network (STN), the downstream primary distribution network is usually modeled as constant load. However, in practical distribution grids, the operators are constantly transferring load from one primary distribution feeder to another one because of, eg, congestion problems or maintenance plans. Considering distribution switching actions can improve the performance of sub‐transmission OPF tool that typically aims at reducing the operation cost of STN. This paper presents a new sub‐transmission Alternating Current (AC) OPF (ST‐AC‐OPF) considering load transferring (LT) between primary distribution feeders implemented through distribution maneuvers. The proposed OPF tool is tested on an illustrative practical example as well as on a real‐world Tehran STN. The numerical results show that the proposed model can obtain a more optimal operating point than conventional ST‐AC‐OPF in terms of the operation cost and load shedding.